Dinamika Perilaku Preventif: Analisis Kritis Persepsi, Kepercayaan, dan Pola Konsumsi Obat Tradisional dalam Menjaga Stamina Masyarakat Desa Sei Beras Sekata Sunggal - Yolanda; Merianti Butar-Butar; Febriati Jelita (Jurnal Kesehatan Sejahtera, 2026)
The use of traditional medicines (herbs) to support the stamina of independent work is very prevalent in suburban areas, but the variation in public perception of the effectiveness and safety of its preparations has not been comprehensively mapped. This study aims to analyze univariately demographic characteristics, knowledge level, benefit perception, safety perception, trust level, frequency of use, and perception of the effectiveness of herbal medicines in maintaining stamina in adult communities in Sei Beras Sekata Village, Sunggal District. This type of research is quantitative with  a cross-sectional descriptive design. The research was conducted in Sei Beras Sekata Village with a sample of 150 adult respondents selected through simple random sampling techniques. Data were collected using a valid and reliable structured questionnaire, then processed using univariate analysis of frequency distribution. The results of the study showed that the majority of respondents had a good level of knowledge (58.7%), a high perception of benefits (64.0%), and a strong sociocultural belief (61.3%) in the existence of herbs. Conversely, perceptions of clinical safety aspects are in the hesitation/less safe zone (54.7%). The pattern of herbal use was dominated by occasional/incidental frequency (48.0%) with the level of perception of post-consumption effectiveness that was considered quite effective (56.0%). The adult community in Sei Beras Sekata Village has high optimism and dependence on herbal medicines to maintain stamina, but is still overshadowed by uncertainty over the standardization of the safety of preparations. Integrative community pharmacy education is very urgent to ensure the safe, rational, and evidence-based use of herbs (evidence-based traditional medicine).